(untitled) (Research, Society and Development, 2021)
This is a documentary study that was carried out from March to December 2019, at a Federal Hospital located in the city of Rio de Janeiro. The data were collected in official documents filed with the Hospital Infection Control Commission sector of the hospital under study. The study aims to: Assess the indicators of adequacy and inadequacy of bladder catheters of delay in a Federal Hospital in the city of Rio de Janeiro. Our objective: Assess the indicators of adequacy and inadequacy of bladder catheters of delay in a Federal Hospital in the city of Rio de Janeiro. Data analysis showed inadequate catheter fixation and, in relation to keeping the collector below the level of the patient away from the floor, and the capacity of the collection bag less than 2/3. We conclude: The data show the importance of reflection for nursing care, the observation of norms and guidelines for infection control, quality of care and patient safety.